Aspek Klinis Central Serous Chorioretinopathy - Fuadi, Anwar; Ali Yafi, Dhanang (Cermin Dunia Kedokteran, 2020)
Central serous chorioretinopathy (CSC) adalah kelainan mata berupa ablasi retina di kutub posterior retina. Berbagai faktor sistemik telah dilaporkan berkaitan dengan CSC. Modalitas teknik pencitraan terkini dapat mengetahui gangguan anatomi dan fungsional pada kasus ringan yang tidak terdeteksi sebelumnya.Â Central serous chorioretinopathy (CSC) is a serous retinal detachment in the posterior pole of the retina. Various systemic factors have been reported to be associated with CSC. Advanced imaging techniques reveal that even a mild case suffer previously undetected anatomic and functional loss.